2002
DOI: 10.1144/gsl.sp.2002.194.01.09
|View full text |Cite
|
Sign up to set email alerts
|

The early evolution and palaeobiogeography of Mesozoic planktonic foraminifera

Abstract: The planktonic foraminifera almost certainly evolved from benthonic ancestors in the early Jurassic. The meroplanktonic genus Conoglobigerina, known from south-central and eastern Europe, appears in the Bajocian and is probably derived from the even more geographically restricted Praegubkinella. This genus was represented by a single taxon in the earliest Toarcian but diversified after the Toarcian anoxic event. At the same level Oberhauserella quadrilobata Fuchs, 1967 became more inflated and there is some ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…It is essential to note that studies of the global diversity of Cretaceous planktonic foraminifers (e.g. Hart 1999;Premoli Silva & Sliter 1999;Hart et al 2002) have shown that anoxic events cannot be described as 'controlling factor' of the evolution of planktonic foraminifers. These studies emphasize that OAE2 is not associated with a drop in foraminifer diversity, but with a major turnover and a slight increase in taxonomic richness.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to note that studies of the global diversity of Cretaceous planktonic foraminifers (e.g. Hart 1999;Premoli Silva & Sliter 1999;Hart et al 2002) have shown that anoxic events cannot be described as 'controlling factor' of the evolution of planktonic foraminifers. These studies emphasize that OAE2 is not associated with a drop in foraminifer diversity, but with a major turnover and a slight increase in taxonomic richness.…”
Section: Discussionmentioning
confidence: 99%
“…tropical/subtropical) facies in the Early Jurassic (Toarcian) (Hart et al 2002). A biostratigraphic analysis has indicated some expansion within the North Atlantic-European region in both the Bajoican-Bathonian and Aptian, but it was not until the latest Albian that a near-global distribution was achieved.…”
Section: Some Geographical Constraints On the Radiationmentioning
confidence: 99%
“…This is almost the same time that the planktic foraminifers appeared in the Tethys Ocean (Wernli, 1995;Wernli and Görög, 1999;Hart et al, 2003Hart et al, , 2012aHudson et al, 2009). The planktic foraminifers did not, however, become diverse and abundant until the Early Cretaceous (Premoli Silva and Sliter, 1999;Hart, 1999;Hart et al, 2002). All of the Jurassic planktic foraminifers appear to have been relatively simple 'globigerine' forms with aragonitic tests (Hart et al, 2012a).…”
Section: Accepted Manuscriptmentioning
confidence: 91%